Existenz - Cronenberg, David, 1943-; Lantos, Robert, 1949-; Hámori, András; Law, Jude, 1972-; Leigh, Jennifer Jason, 1962-; Holm, Ian, 1931-2020; Dafoe, Willem; Polley, Sarah (Miramax : Echo Bridge Home Entertainment, 2012)
A designer of a virtual reality game is hunted by an assassin intent on killing her and destroying her creation.